2020
DOI: 10.1186/s12883-020-01999-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting prehospital delay in rural and urban patients with stroke: a prospective survey-based study in Southwest Germany

Abstract: Background Reducing prehospital delay plays an important role in increasing the thrombolysis rate in patients with stroke. Several studies have identified predictors for presentation ≤4.5 h, but few compared these predictors in urban and rural communities. We aimed to identify predictors of timely presentation to the hospital and identify possible differences between the urban and rural populations. Methods From January to June 2017, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…We identified 67 studies addressing pre-hospital organizational factors associated with delay or access to ART ( Appendix A - Table A3 ). Activation of stroke code, pre-hospital notification and use of pre-hospital emergency services [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], mobile stroke units [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], implementation of specific electronic apps to insert and share clinical data with the hospital stuff [ 33 ], use of ambulance [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], telestroke [ 47 , 48 ], implementation of specific pre-hospital protocols [ 49 , 50 ], education campaigns […”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 67 studies addressing pre-hospital organizational factors associated with delay or access to ART ( Appendix A - Table A3 ). Activation of stroke code, pre-hospital notification and use of pre-hospital emergency services [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], mobile stroke units [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], implementation of specific electronic apps to insert and share clinical data with the hospital stuff [ 33 ], use of ambulance [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], telestroke [ 47 , 48 ], implementation of specific pre-hospital protocols [ 49 , 50 ], education campaigns […”
Section: Resultsmentioning
confidence: 99%
“…Under-recognition or delays in recognition of stroke symptoms are consistently identified as one of the main causes of pre-hospital delays [ 8 , 16 ]. Hence, with no surprise, population campaigns focused on stroke recognition, severity and existence of treatment emerged as a common factor to promote ART [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 23 , 34 , 36 , 38 , 39 , 40 , 41 , 46 , 48 , 103 , 104 , 105 , 106 , 107 , 108 ]. Sustainable levels of population awareness may only be achieved by continuous education campaigns, probably at least six months each [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor stroke knowledge was associated with greater presentation delay in some studies (Chen et al, 2007;Zerwic et al, 2007), while in contrast, other studies found that having a previous history of stroke or stroke knowledge was associated with less presentation delay (Kitko et al, 2008;Ungerer et al, 2020). Still, others found that having stroke knowledge did not decrease presentation delay (Faiz et al, 2013).…”
Section: Key Findings and Gaps In The Existing Literaturementioning
confidence: 92%
“…When examining the literature relating to EHS use following a stroke, presentation delay emerged as a central concept. A total of ten studies that examined the association of different determinants with presentation delay were captured in this review, of these three were qualitative (Kitko et al, 2008;Moloczij et al, 2008;Zerwic et al, 2007) and seven were quantitative (Chen et al, 2007;Ekundayo et al, 2013;Faiz et al, 2013;Geffner et al, 2012;Memis et al, 2008;Seremwe et al, 2017;Ungerer et al, 2020). These are summarized in Table 3 at the end of this section.…”
Section: Factors Influencing Presentation Delaymentioning
confidence: 99%
See 1 more Smart Citation